2014
DOI: 10.1177/1362361314536625
|View full text |Cite
|
Sign up to set email alerts
|

Depression and its measurement in verbal adolescents and adults with autism spectrum disorder

Abstract: In a sample of 50 verbally fluent adolescents and adults with autism spectrum disorders (ASD) (age: 16-31 years; verbal IQ: 72-140), we examined the pattern of response and associations between scores on common measures of depressive symptoms, participant characteristics, and clinical diagnosis of depressive disorders. Beck Depression Inventory, 2nd edition (BDI-II) item descriptives in this ASD sample were compared to previously published data from a large typically developing sample, with results suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 47 publications
7
112
0
Order By: Relevance
“…Findings from this and other studies highlight the lack of appropriately validated measures to assess mental health problems in adults with autism (Brugha et al, in press;Gotham et al, 2015) and, without these, affected individuals are less likely to receive appropriate diagnostic and intervention services. However, the scarcity of professionals who have expertise in diagnosing and treating mental health problems in individuals with autism remains a major challenge (Underwood et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Findings from this and other studies highlight the lack of appropriately validated measures to assess mental health problems in adults with autism (Brugha et al, in press;Gotham et al, 2015) and, without these, affected individuals are less likely to receive appropriate diagnostic and intervention services. However, the scarcity of professionals who have expertise in diagnosing and treating mental health problems in individuals with autism remains a major challenge (Underwood et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…44,45 The availability of better-tailored services could decrease lengthier (thus more costly) service use. We need instrument validation for depression assessment in this population, 33 and it likely will be valuable to widen our scope beyond categorical comorbidity to the pervasive issue of affective distress in ASD. We know little about internalizing phenomenology or prevalence in the early and late phases of development within DD populations.…”
Section: Discussionmentioning
confidence: 99%
“…These instruments generally have been found to have high sensitivity but low specificity for emotional health disorders in some samples with ASD, 32,33 and, by contrast, to under-report emotional health problems in comparison to self- and teacher-report ASEBA versions in ASD. 34 We modeled ASEBA variables for all participants, regardless of language level, after our preliminary findings indicated that neither verbal IQ nor ADOS module was related to rate of anxious/depressive symptom growth, our primary outcome of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive symptoms of depression (e.g. negative attributions) are more prevalent than affective or somatic symptoms in those with ASD compared to the general population (Gotham et al 2015). Accordingly, there may be subtle but important differences in the relationship between ASD, depression and suicidality, including specific depression profiles that may be associated with an increased risk.…”
Section: Personal Traits: Depression and Anxietymentioning
confidence: 99%